Arecaceae endémicas del Perú - Millán, Betty (2006)
Thirty genera and 155 species of palms are known from Peru (Brako & Zarucchi, 1993). Here we recognize nine endemic species in six genera. These endemic taxa occupy the Humid Amazonian, and Montane Forest ecological regions, between 130 and 3000 m elevation. Three of these species have been recorded within a protected area.